Cathepsin K levels in the crevicular fluid of dental implants: a pilot study - Georg D. Strbac (journal of clinical periodontology, 2006)
Objective: To determine the concentration of cathepsin K secreted into the crevicular fluid around dental implants and its correlation with clinical parameters of healthy implants and implants showing clinical signs of peri-implantitis. Material and Methods: Nineteen patients with 40 implants with and without periimplantitis were enrolled in the study. Peri-implantitis was diagnosed by the pocket probing depth (PD), the modified bleeding index (MBI), the modified plaque index (MPI) and by radiographic signs of bone loss. Gingival crevicular fluid collected from the buccal and lingual sites was adsorbed to filter strips. Cathepsin K levels and total protein within the crevicular fluid were determined by immunoassay and the bicinchoninic method, respectively. Results: Cathepsin K per filter strip normalized to the time of collection was 10.1 (0–33.5) pmol/sample around control implants and 22.4 (3.7–56.3) pmol/sample in the peri-implantitis group. The difference between the medians was significant (po0.01). Absolute cathepsin K levels in the crevicular fluid of all implants investigated showed a positive correlation with PD (R50.25; p50.03), MPI (R50.28; p50.01) and MBI (R50.32; po0.01). Absolute cathepsin K levels in the crevicular fluid also correlated with the adsorbed volume of gingival crevicular fluid (R50.51; po0.01). When normalized to the adsorbed volume of gingival crevicular fluid, the concentration of cathepsin K was 2.2 (0.01–6.4)nM around control implants and 1.7 (0.4–4.6)nM in the peri-implantitis group (p50.33). Patients’ age correlated with sample volume and with cathepsin K normalized to the adsorbed volume of gingival crevicular fluid (R50.39; po0.01). Moreover, significant differences between male and female (po0.01, po0.01), and between mandible and maxilla (po0.05, po0.01), but not between buccal and lingual sites (p50.99, p50.93), were observed when analysed for the parameters adsorbed volume and absolute cathepsin K levels. Conclusion: Clinical parameters of peri-implantitis are associated with a higher amount of cathepsin K and a higher volume adsorbed to filters strips. To establish cathepsin K as a biochemical parameter to monitor peri-implant tissue health, age, sex and collection site should be considered to avoid interfering influences because of sample inhomogenity. Also a prospective study over time including more patients would be necessary.